Inflation and policy response: A case study of Indonesia during the Covid-19 pandemic - Erdyana Eka Briza; Nugroho Ris Yuwono Yudo (BIO Web of Conferences)
Through the responses and contributions generated during the COVID-19 pandemic from March 2020 to April 2023, this research aims to analyse the monetary determinants of inflation in Indonesia. The dependent variables in this research include consumer price index inflation (CPI) and core inflation. In contrast, the independent variables are variables on the monetary side, which include interest rate policy, money supply (M2), and the exchange rate of the United States dollar against the rupiah. This research uses a quantitative approach with the Vector Error Correction Model (VECM) as the analysis method. According to the research findings, CPI and core inflation responded negatively to shocks in policy interest rates. Both CPI and core inflation responded positively to shocks or changes in the money supply. CPI and core inflation respond positively to money supply shocks. CPI and core inflation respond negatively to exchange rate shocks. Overall, core inflation responded better to the magnitude of changes in monetary side variables during the COVID-19 pandemic than consumer price index (CPI) inflation. The interest rate policy variable contributes more to consumer price index (CPI) inflation and core inflation than the money supply and exchange rate variables.